CBIO-01. TRANSCRIPTIONAL MODULATION OF BRACHYURY IN CHORDOMA - Seldomridge, Ashlee (Neuro Oncol, 2017)
INTRODUCTION: Brachyury, a transcription factor involved in mesoderm specification, is essential for chordoma growth. Expression of brachyury in epithelial cancers is associated with poor prognosis in part due to its role in mediating the epithelial-mesenchymal transition (EMT); brachyury is virtually absent in normal tissues beyond embryogenesis. TG02 is a multikinase inhibitor that targets RNA polymerase II by inhibiting CDK9. Because chordoma cells are dependent on brachyury for survival, we investigated the potential therapeutic strategy of transcriptional modulation of brachyury using TG02. Our previous work indicated that very high brachyury levels may reduce the susceptibility of carcinoma cells to immune-mediated lysis, we therefore investigated the effect of TG02 treatment on chordoma cell lysis by immune effector cells. METHODS/ RESULTS: In vitro expression of brachyury protein in chordomas was consistently high. TG02 exposure down-regulated cell proliferation and brachyury in a time- and dose-dependent manner with clinically achievable concentration (10 nM). Combined cycloheximide and TG02 treatment further decreased brachyury protein, suggesting that brachyury downregulation is modulated at RNA/protein synthesis, not protein degradation. Furthermore, TG02 treatment of chordoma cells impaired migration, invasion, and cell cycle progression through G(2)-M phase. Single-sample geneset enrichment analysis performed on an independent mRNA expression dataset (GSE68497) of chordoma cell lines revealed strong correlation of T gene expression (encoding for brachyury) to activity scores of several tumor invasiveness genesets (T corr: 0.919). Expression of vimentin and fibronectin, both associated with EMT, was also suppressed within 4 hours of TG02 treatment and persisted. Short-term exposure of tumor cells to low-dose TG02 enhanced tumor lysis mediated by natural killer cells and studies are ongoing to evaluate the effect on lysis by brachyury-specific CD8+ T cells. CONCLUSIONS: Inhibition of CDK9 transcriptionally modulates brachyury expression, reverts mesenchymal features, enhances cell-based immunotherapy, and represents a potential novel therapeutic strategy for chordoma and other transcriptionally driven cancers.